Kyai as Moral Authority: Negotiating Religious Discipline and Cultural Identity in Pesantren - Titi Sartini (Managere: Indonesian Journal of Educational Management, 2025)
This study investigates the role of Kyai in shaping religious culture within Islamic boarding schools (pesantren). Specifically, it examines how Kyai's leadership influences the spiritual development of students, both through personal example and direct instructions. The research addresses the gap in existing literature regarding the broader impact of Kyai's leadership on fostering a religious environment, extending beyond administrative functions to encompass cultural and social aspects. The research employed a qualitative approach, using in-depth interviews, participant observations, and documentation to gather data from Kyai, teachers, and students at a pesantren in Indonesia. The study identifies key leadership practices, such as leading communal prayers and providing spiritual guidance, that contribute to developing a religious culture. Findings suggest that Kyai's example, combined with direct instructions on religious practices and social behavior, is crucial in instilling a deep sense of religious discipline among students. This research contributes to a more nuanced understanding of spiritual leadership in Islamic education and has implications for developing effective leadership models in religious institutions. The findings also open avenues for future studies exploring the long-term impact of spiritual leadership on student development in pesantren contexts.